1989
DOI: 10.1111/j.1464-0597.1989.tb01207.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Charitable Behaviour with Compliance Techniques

Abstract: Pour comparer I'impact de trois techniques d'acquiescement sur I'incitation au comportement charitable, on a demand6 A 409 personnes de verscr $2 a l ' h e r i c a n Cancer Society. Cette requtte fut immtdiatement prksentte dans trois groupes contrde et p r t d d t e dans neuf groupes expenmentau d'une demande prtliminaire correspondant A une proctdure d'aquiescement B requite multiple. On a d'abord demand6 aux sujets soumis A la technique "pied dans la porte" de ripondre 3 un questionnaire composk de 10, 35 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 24 publications
2
12
0
1
Order By: Relevance
“…This ploy led to more contributions and contributions for higher amounts of money than were obtained in comparison conditions. Wang et al (1989) obtained similar results in a door-to-door campaign for the American Cancer Society. Whereas foot-in-the-door, door-in-the-face, and low-ball are general compliance techniques that researchers have sometimes adapted to induce charitable donations, there is one technique that is specifically designed to induce such contributions.…”
Section: Verbal Requests For Charitable Contributionssupporting
confidence: 84%
See 3 more Smart Citations
“…This ploy led to more contributions and contributions for higher amounts of money than were obtained in comparison conditions. Wang et al (1989) obtained similar results in a door-to-door campaign for the American Cancer Society. Whereas foot-in-the-door, door-in-the-face, and low-ball are general compliance techniques that researchers have sometimes adapted to induce charitable donations, there is one technique that is specifically designed to induce such contributions.…”
Section: Verbal Requests For Charitable Contributionssupporting
confidence: 84%
“…Goldman (1985) found that when a telephone interviewer first asked people to make 150 calls on behalf of "Friends of the Zoo" and was refused, people were then more likely to comply with a request to stuff and address 75 envelopes than were people who were not asked the initial large request. In separate campaigns for an art museum (Brownstein & Katzev, 1985) and the American Cancer Society (Wang, et al, 1989) the door-in-the-face technique was more effective in inducing donations than was the foot-in-the-door technique. Cantril (1991) successfully used the door-in-the-face technique to gain verbal compliance with requests to solicit organ donors or to work with the elderly.…”
Section: Verbal Requests For Charitable Contributionsmentioning
confidence: 96%
See 2 more Smart Citations
“…With other techniques (foot-in-the-door, asking for a signature on a petition, and door-in-the-face, asking for a five-dollar contribution initially), solicitors were not able to raise as much from the eightynine subjects in the study. Wang, Brownstein, and Katzev (1989) compared the relative impact of three social compliance techniques in promoting charitable behavior. Those asking prospects to donate either $10, $25, or $50 up front (door-in-the-face) produced more money than either having the prospect answer a questionnaire or asking for an amount of $1.50 or less.…”
Section: The Management Of Fundraisingmentioning
confidence: 99%